(3MOjbI GdCRgGQ aj TQM eGgjI GdYTH hGdYbGQs - (3bGSe Hf eMeO Hf EHQGgje GdhRjQ GdZSGfj, GdhRjQ,J (B1019 (3g` s
(3ChdgG (B:s
(3GeG HYO JfGbdJ CfUGQ GdYde ajV Gddg dg SjOfG CejQ GdeDefjf s
(3BNQgG (B:s
(3TLQI GdRjJhf , hbO JbOe TQMgG ai HGH GdRGj s
(3HChdgG JQLeI ddeDdas
(3GdeDda hdO SfI (B960 (3g`s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B182s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGJi (B- (3U (B81 s
Keywords: (3GdWHs